2014
DOI: 10.3727/096368913x665585
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Interaction between Human Multipotent Adult Progenitor Cells and NK Cells

Abstract: Human multipotent adult progenitor cells (hMAPCs) are isolated from bone marrow with a more extensive expansion capacity compared to human mesenchymal stem cells (hMSCs) and with the ability to differentiate into endothelium. Like hMSCs, hMAPCs inhibit T-cell proliferation induced by alloantigens. In this study, we tested the interaction between hMAPCs and natural killer (NK) cells. We assessed the susceptibility of hMAPCs to NK cell-mediated lysis and the immunomodulation of hMAPCs on NK cell function during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…Like MSCs, MAPC cells have potent immunomodulatory effects in T cells [12][13][14], are nonimmunogenic for T-cell proliferation and cytokine production and even suppress T-cell activation and proliferation induced by alloantigens and mitogens in vitro. Human MAPC cells also have inhibitory effects in natural killer cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…Like MSCs, MAPC cells have potent immunomodulatory effects in T cells [12][13][14], are nonimmunogenic for T-cell proliferation and cytokine production and even suppress T-cell activation and proliferation induced by alloantigens and mitogens in vitro. Human MAPC cells also have inhibitory effects in natural killer cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the T‐cell antigen‐specific cytotoxic activity (13.50% ± 3.71%) against EBV + B cells was significantly higher than the specific lysis of MultiStem. In some experiments ( n = 4), MultiStem cells were pretreated with interferon‐γ (IFN‐γ) (100 U/ml; Roche Diagnostics, Vilvoorde, Belgium, http://www.roche.com) for 48 hours to increase MHC class I molecule expression [28, 29]. However, this upregulation did not result in a higher sensitivity to CTL‐mediated lysis, confirming the immune‐privileged status of these clinical‐grade hMAPCs (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Given the fact that MAPCs are among the noteworthy mesenchymal cell populations for clinical usage and have the advantage over MSCs of having large‐scale manufacturing and banking potential and therefore prompt availability, it is important to understand how these clinical‐grade MAPCs (MultiStem) interact with immune cells to validate their widespread therapeutic applicability. We found that hMAPCs are nonimmunogenic for alloreactive T‐cell proliferation; they impair allogeneic proliferative T‐cell responses, and they mutually interact with allogeneic NK cells in vitro [28, 29]. In this study, the influence of MultiStem cells on the cytotoxic function of CD8 + T cells was assessed by evaluating the immunogenicity of MultiStem and the susceptibility of the stem cell population toward CTL‐mediated lysis and by analyzing the MultiStem‐mediated modulation of CTL functionality.…”
Section: Introductionmentioning
confidence: 99%
“…This immunoregulation is mainly described as the suppression of regulatory T cells in vitro [16] while the interaction with neutrophils, the most important effector cell in IRI, is largely unexplored. MSC and MAPC share similar immunoregulatory capabilities, although MAPC cells are found to be more potent compared to MSC in rhesus monkeys [32], human MSC and MAPC share similar immunoregulatory capabilities [23, 26, 33]. However, MAPC cell therapy is privileged over MSC for clinical translation since their low senescence and high population doubling allows for banking of large batches of cells from a single donor [15].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we chose this cell type as bone marrow-derived cellular treatment for attenuation of ischemia-reperfusion injury in lung transplantation. Also, xenotransplantation and allotransplantation of these cells is thought to be safe due to a low expression of MHC I and lack of MHC II expression [14, 33]. These immune-privileged properties avoid recognition by the recipient’s immune system, and therefore, this immune mismatch is generally believed not to be an increased risk for patients.…”
Section: Discussionmentioning
confidence: 99%